2002
DOI: 10.1046/j.1540-8175.2002.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Left Ventricular Outflow Tract Obstruction in the Setting of Acute Anterior Myocardial Infarction: A Serious and Potentially Fatal Complication?

Abstract: Dynamic left ventricular outflow tract (LVOT) obstruction was thought to be a hallmark of hypertrophic obstructive cardiomyopathy, especially in those cases with isolated asymmetric septal hypertrophy and systolic anterior motion (SAM) of the mitral valve. Recently, several authors described the occurrence of a dynamic LVOT obstruction during acute coronary insufficiency in ventricles without significant myocardial hypertrophy. The LVOT gradient was reported to disappear following resolution of the ischemic sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 5 publications
2
27
0
1
Order By: Relevance
“…This is consistent with the clinical observation that patients with anterior AMI may occasionally develop significant LVOT obstruc- tion, especially during catecholamine infusion [1][2][3][4][5]. The significant relationship between reduced mitral annular size and the provoked LVOT obstruction by dobutamine infusion in the presence of anterior AMI is also consistent with the previous observation that excessive mitral leaflets beyond coaptation is the critical factor to cause LVOT obstruction or SAM in patients with hypertrophic cardiomyopathy [7][8][9][10][11].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is consistent with the clinical observation that patients with anterior AMI may occasionally develop significant LVOT obstruc- tion, especially during catecholamine infusion [1][2][3][4][5]. The significant relationship between reduced mitral annular size and the provoked LVOT obstruction by dobutamine infusion in the presence of anterior AMI is also consistent with the previous observation that excessive mitral leaflets beyond coaptation is the critical factor to cause LVOT obstruction or SAM in patients with hypertrophic cardiomyopathy [7][8][9][10][11].…”
Section: Discussionsupporting
confidence: 90%
“…This study further demonstrated that reduced anteroposterior dimension of the mitral annulus with augmented basal posterior LV contraction is related to the provoked LVOT obstruction by dobutamine infusion in the presence of anterior AMI. Utility LVOT obstruction following catecholamine infusion in anteroseptal AMI causes serious hemodynamic deterioration [1][2][3][4][5]. This study has demonstrated a potential relation between the provoked LVOT obstruction and reduced antero-posterior mitral annular dimension with hyperdynamic basal posterior LV wall.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…However, there have been some reports of patients with transient intraventricular obstruction during AMI who experienced myocardial rupture and subsequently died as a result. 3,6 Dynamic intraventricular obstruction is initially diagnosed with the detection of a new ejection systolic murmur, as in this case. Mitral regurgitation and ventricular septal perforation are well-recognized complications of AMI with a new systolic murmur.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, there have been some reports of dynamic intraventricular obstruction in the setting of AMI that resulted in a systolic murmur. [1][2][3][4][5][6][7] Moreover, dynamic intraventricular obstruction could be associated with a catastrophic medical outcome. We report a case of transient dynamic intraventricular obstruction in AMI following administration of cilostazol.…”
mentioning
confidence: 99%